2018
DOI: 10.1021/acsami.8b02799
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Granular Structure and the Enhancement of Electron Field Emission Properties of Nanocrystalline and Ultrananocrystalline Diamond Films Due to Plasma Treatment Process

Abstract: The present work reports the plasma post treatment (ppt) process that instigates the evolution of granular structure of nanocrystalline diamond (NCD), consequently conducing the enhancement of the electron field emission (EFE) properties. The NCD films contain uniform and nanosized diamond grains (∼20 nm) with negligible thickness for grain boundaries that is distinctly different from the microstructure of ultrananocrystalline (UNCD) films with uniformly sized ultrananodiamond grains (∼5 nm) having relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
1
13
1
1
Order By: Relevance
“…Hence, a material with better robustic and high secondary electron emission efficiency is essential to act as a microplasma device’s cathode. Theoretical studies reported that a superior FEE material can show a better performance in a microplasma device when it is utilized as a cathode. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, a material with better robustic and high secondary electron emission efficiency is essential to act as a microplasma device’s cathode. Theoretical studies reported that a superior FEE material can show a better performance in a microplasma device when it is utilized as a cathode. , …”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystalline diamond (NCD) films containing 10–100 nm-sized diamond grains were synthesized by the addition of noble gases in the CH 4 /H 2 microwave plasma. , Especially, addition of Ar leading to a H 2 -deficient plasma enhances the electron density and modifies the diamond film morphology from MCD to NCD (or ultrananocrystalline diamond (UNCD)) films. The transition in microstructure was proposed to be induced by changing the growth mechanism governed by CH 3 species in a CH 4 /H 2 plasma , to C 2 as a growth species in CH 4 /Ar plasma. , The decrease in grain size of diamond in the NCD film enhances the proportion of nondiamond carbon in the grain boundaries, and hence, it shows better FEE properties than the MCD films …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dopants such as nitrogen 13 and oxygen 14,15 have also been reported to introduce into UNCD films, which provide electrons for EFE in diamond grains. Moreover, various dopants such as Ar, 16 N 2 , 17 and N 2 and PH 3 18 mix-gas were directly added during the CVD synthesis to enhance the EFE properties by inducing an amount of the graphite phase or improving the microstructure. 19 The introduction of large impurity atoms would damage the lattice of grains and influence the quality of films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Coating CNTs with wide bandgap (WBG) materials, which are able to reduce the effective work function and provide mechanical protection for the sharp emitters, has been considered as one of the most successful approaches to increase the stability of CNTs’ FE current while keeping a low applied driving voltage. Besides widely used oxides such as silicon dioxide, magnesium oxide, zinc oxide, or titanium dioxide, sp 3 -bonded carbon materials are strong candidates for this coating, for instance, ultranano­crystalline diamond (UNCD) or diamond-like carbon (DLC) , films. It has been undoubtedly verified that sp 3 coatings stabilize, and even improve, the CNT FE currents, owing to their favorable properties, such as low or even negative electron affinity (LEA or NEA), mechanical strength, and radiation tolerance. , However, the FE enhancement induced by sp 3 coatings, which refers to a decrease of turn-on fields hereinafter, was not inevitable. , It has been suggested by extensive studies that there is a relationship between the coating thicknesses and turn-on fields.…”
Section: Introductionmentioning
confidence: 99%